Total Factor Productivity (TFP) of Textile Industry and Textile Products in Indonesia for the Period 2005-2009 - Kurniawaty, Henny (Department of Economics, Faculty of Economics and Business, Universitas Airlangga, 2016)
The Textile Industry and Product (TPT) are one of the industries that have export orient and has a market target or has a huge role in creating PDB of non-oil and natural gas manufacture industry. The main aspect to solve the work of TPT industry sector are the efficiency aspect, high productivity, and technological progress. This study counts the growth of Total Factor Productivity (TFP) in the industry of TPT in Indonesia from 2005 to 2009 by using panel data firm level. The growth count of TFP used Stochastic Analysis Frontier (SFA) method with 2 models, Cobb-Douglas and Translog's model. The development of TFP is decomposed into 3 components: technical efficiency change, technical change, and scale efficiency change. The average growth rate of TFP in the industry of TPT in Indonesia is 2 percent. The major establishment component of growth formation of TFP is technical change, in which the average rate is over 1 percent, while the average technical efficiency change is 1 percent. It shows that the efficiency is stable or it does not change from time to time and for the average rate scale efficiency change is very tinny, it is under 1 percent. The influence of wages on the growth of TFP is very tinny; besides, the foreign property influences the growth of TFP in the industry of TPT in Indonesia.